Avaliação das características clínicas e sócio demográficas dos pacientes com amputações de membros inferiores em nível maior e menor no município de Aracaju/SE - Reis, Daniele Cristine dos (2016)
Objective: To evaluate the clinical and demographic characteristics of patients with lower and upper limb amputations in the city of Aracaju / SE. Method: This is a cross- sectional study, developed in the year 2015-2016 at the Basic Health Units - UBS of Aracaju, with adult patients submitted to lower limb amputation. Results: A total of 225 individuals with lower limb amputations were identified, with a median age of 66 years, of which 53% (120/225) were male and 47% (105/225) female. The diabetic foot was the most frequent etiology, reaching 70% (158/225) of the cases. There were no significant differences regarding the characteristics related to the housing company (p = 0.264) and the presence of home care (p = 0.340). There were also no differences in relation to the amputated limb (p = 0.987), although some differences were detected according to the segment level (p <0.001) with a slightly higher frequency in relation to the thigh and fingers segment in the Group of other diagnoses. There was a low frequency of physiotherapy and proteolysis of these patients and no differences were observed between the two groups (p = 0.104 and p = 0.171, respectively). Regarding the clinical characteristics, a significantly higher frequency of diabetes mellitus (p <0.001) and systemic arterial hypertension (p = 0.002) were detected among diabetic foot amputees. Conclusion: The study points to diabetes as one of the most prevalent causes of amputation. The small percentage of amputees in the rehabilitation services and using a prosthesis is noteworthy.